Geoenvironmental assessment of magnesite deposit Jelsava - Dúbrava massif - CICMANOVÁ, SONA (Boletim Paranaense de Geociências, 2002)
This article gives basic information on two main groups of geoenvironmental impacts originated from mining and processing activities realised on magnesite deposit of the Jelsava - Dúbrava massif: mining impacts from magnesite exploitation and impacts from magnesite processing. They differ in character (nature), time behaviour and scale.